(untitled) (Journal of Human Sciences, 2023)
The study aimed to identify the role of educational institutions in the most successful sponsorship of people with special needs from the point of view of teachers. The study followed the descriptive survey method. The study used a questionnaire consisting of (14) items to collect its data, and it consisted of two axes: Educational services and guidance, and cooperation with relevant bodies and institutions, its validity and reliability were confirmed. The study sample consisted of (34) male and female teachers who were chosen randomly. The results of the study showed that the role of educational institutions in sponsoring people with special needs was the most successful from the point of view of the study community, with a (moderate) degree in all fields. Where the arithmetic mean was (3.38), and the field of "educational services and counseling" had a (moderate) degree, with an arithmetic mean of (3.28(. In addition, that the field of "cooperation with relevant bodies and institutions" was at a (moderate) degree, with an arithmetic mean of (3.47), The researchers also recommended "training, developing and developing the capabilities and thinking of people with disabilities and special needs in accordance with the necessities, requirements and developments of life, taking into account their differences in needs, by establishing rehabilitation and training centers."